Curable composition and electrical component

By using compositions of heterocyclic (meth)acrylate, alicyclic (meth)acrylate and (meth)acrylate containing oxygen atoms in electrical components, adhesion and (meth)acrylate in prior art are solved. The problem of insufficient strength achieves efficient sealing and corrosion-proofing effects on metal surfaces.

CN119256029APending Publication Date: 2025-01-03DKS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042621.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing curable compositions have not been fully resolved in improving the adhesion and strength of metal surfaces of electrical components, especially in improving the adhesion without damaging the strength.

Method used

Using a composition of heterocyclic (meth)acrylate, alicyclic (meth)acrylate and (meth)acrylate containing oxygen atoms, an excellent curing is formed by adjusting its molecular weight and functional group number. A resin composition for sealing and corrosion protection of electrical components.

Benefits of technology

It achieves significant improvement in adhesion and strength, can effectively prevent metal corrosion, and improve adhesion and flexibility to metal without damaging strength, and is suitable for the covering and sealing of electrical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150764320000051
    Figure BDA0005150764320000051
  • Figure BDA0005150764320000131
    Figure BDA0005150764320000131
  • Figure BDA0005150764320000151
    Figure BDA0005150764320000151
Patent Text Reader

Abstract

Provided is a curable composition having excellent adhesion and strength. A curable composition according to an embodiment includes (A) a heterocyclic (meth) acrylate having a five-membered or six-membered heterocyclic ring containing an oxygen atom, (B) an alicyclic (meth) acrylate, and (C) a (meth) acrylate other than the component (A) and the component (B), the (meth) acrylate having a molecular weight or a weight-average molecular weight of 200-30,000 and a functional group number of 1 or 2. The total content of the component (A) and the component (B) is 70-95 parts by mass per 100 parts by mass of the total content of the components (A)-(C). The mass ratio (A) / (B) of the content of the component (A) to the content of the component (B) is 0.6-20.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable composition and an electrical component using the same. Background Art

[0002] In electrical components, exposed metal parts such as terminals are coated or sealed with resin to prevent metal corrosion. As the resin composition for corrosion protection of such electrical components, a curable composition that cures by heat or light is used.

[0003] Patent Document 1 discloses a thermosetting composition comprising polybutadiene having a (meth)acryloyl group at a terminal and a thermal polymerization initiator as a thermosetting composition capable of forming a cured product having excellent sealing properties. Patent Document 1 discloses that a (meth)acrylate compound, particularly a (meth)acrylate compound having an alicyclic hydrocarbon group bonded thereto in the form of an ester bond, can be used in combination.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-54902 Summary of the invention

[0007] Technical problem that the invention aims to solve

[0008] However, Patent Document 1 does not disclose using an oxygen-containing heterocyclic (meth)acrylate together with an alicyclic (meth)acrylate and combining these with a (meth)acrylate having a specific molecular weight at a predetermined ratio.

[0009] Curable compositions for preventing metal corrosion in electrical components are required to have excellent adhesion to metals, but conventional curable compositions have not been able to sufficiently improve adhesion without sacrificing strength.

[0010] In view of the above, an object of an embodiment of the present invention is to provide a curable composition having excellent adhesion and strength.

[0011] Technical solutions to the problem

[0012] The present invention includes the following embodiments.

[0013] [1] A curable composition comprising: (A) a heterocyclic (meth)acrylate having a five-membered or six-membered heterocyclic ring containing an oxygen atom; (B) an alicyclic (meth)acrylate; and (C) a (meth)acrylate other than the above-mentioned components (A) and (B), having a molecular weight or a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2, wherein the total content of the above-mentioned components (A) and (B) is 70 to 95 parts by mass relative to 100 parts by mass of the total content of the above-mentioned components (A), (B) and (C), and the mass ratio (A) / (B) of the content of the above-mentioned component (A) to the content of the above-mentioned component (B) is 0.6 to 20.

[0014] [2] The curable composition according to [1], comprising, as the component (C), a (meth)acrylate having a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2 and containing a polybutadiene structure.

[0015] [3] The curable composition according to [1], comprising, as the component (C), a urethane (meth)acrylate having a molecular weight or a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2.

[0016] [4] The curable composition according to [1], comprising as the component (C) a (meth)acrylate having a polybutadiene structure and a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2, and a urethane (meth)acrylate having a molecular weight or a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2.

[0017] [5] The curable composition according to any one of [1] to [4], wherein the heterocyclic ring of the component (A) is a saturated heterocyclic ring.

[0018] [6] The curable composition according to any one of [1] to [5], wherein the total content of the component (A), the component (B) and the component (C) is 80% by mass or more relative to 100% by mass of the curable composition.

[0019] [7] The curable composition according to any one of [1] to [6], which is used for electric parts.

[0020] [8] A cured product obtained by curing the curable composition as described in any one of [1] to [7].

[0021] [9] An electrical component comprising the cured product described in [8].

[0022] Effects of the Invention

[0023] According to the embodiment of the present invention, a curable composition having excellent adhesion and strength can be provided. DETAILED DESCRIPTION

[0024] The curable composition of the present embodiment is a curable resin composition containing the following (A) component, (B) component, and (C) component.

[0025] (A) Heterocyclic (meth)acrylate containing oxygen atom

[0026] (B) Alicyclic (meth)acrylate

[0027] (C) (Meth)acrylates other than the above-mentioned components (A) and (B)

[0028] In this specification, "(meth)acrylate" means at least one of acrylate and methacrylate. "(Meth)acrylic acid" means at least one of acrylic acid and methacrylic acid. "(Meth)acryloyl" means at least one of acryloyl and methacryloyl. "(Meth)acryloyloxy" means at least one of acryloyloxy and methacryloyloxy.

[0029] [(A) Heterocyclic (meth)acrylate]

[0030] In the present embodiment, as component (A), a heterocyclic (meth)acrylate having a five-membered ring or a six-membered ring heterocyclic ring containing an oxygen atom (hereinafter referred to as heterocyclic (meth)acrylate (A)) is used. Heterocyclic (meth)acrylate (A) is a compound having the above-mentioned heterocyclic ring and a (meth)acryloyl group in the molecule. Heterocyclic (meth)acrylate (A) contributes to improving the adhesion to metal.

[0031] The above heterocyclic ring may be saturated or unsaturated, but is preferably a saturated heterocyclic ring. The above heterocyclic ring may have one or two oxygen atoms as heteroatoms. The above heterocyclic ring may have only oxygen atoms as heteroatoms, or may have other heteroatoms such as nitrogen atoms or sulfur atoms while having oxygen atoms. Preferably, the heteroatoms are only oxygen atoms. Specific examples of the above heterocyclic ring include tetrahydrofuran ring, dioxolane ring, tetrahydropyran ring, 1,2-dioxane ring, 1,3-dioxane ring, 1,4-dioxane ring, etc.

[0032] The heterocyclic (meth)acrylate (A) may be a multifunctional (meth)acrylate having a plurality of (meth)acryloyl groups, preferably a monofunctional (meth)acrylate having one (meth)acryloyl group. In the heterocyclic (meth)acrylate (A), the (meth)acryloyloxy group may be directly bonded to the carbon atom of the heterocyclic ring or may be bonded via a connecting group. In one embodiment, the (meth)acryloyloxy group may be bonded to the heterocyclic ring via an alkanediyl group having 1 to 6 carbon atoms, for example, via a methylene group. In addition to substitution based on the (meth)acryloyloxy group, the heterocyclic ring may further have a substituent or may be unsubstituted. There is no particular limitation on the substituent, and a hydrocarbon group is preferred. For example, the heterocyclic ring may have one or more hydrocarbon groups (such as alkyl groups) having 1 to 6 carbon atoms as substituents.

[0033] Examples of the heterocyclic (meth)acrylate (A) include:

[0034] (A1) a group having a (meth)acryloyloxy group bonded to a substituted or unsubstituted tetrahydrofuran ring via an alkanediyl group having 1 to 6 carbon atoms (e.g., tetrahydrofurfuryl (meth)acrylate),

[0035] (A2) a (meth)acryloyloxy group bonded to a substituted or unsubstituted dioxolane ring via an alkanediyl group having 1 to 6 carbon atoms (e.g., (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate),

[0036] (A3) a (meth)acryloyloxy group bonded to a substituted or unsubstituted dioxane ring via an alkanediyl group having 1 to 6 carbon atoms (for example, cyclic trimethylolpropane formal (meth)acrylate),

[0037] (A4) Substituted or unsubstituted tetrahydrofurfuryl alcohol (meth) acrylic acid polymer ester

[0038] Etc. These may be used alone or in combination of two or more.

[0039] In one embodiment, the heterocyclic (meth)acrylate (A) may be at least one selected from the group consisting of tetrahydrofurfuryl (meth)acrylate, methyl (2-methyl-2-ethyl-1,3-dioxolan-4-yl) (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, and tetrahydrofurfuryl alcohol (meth)acrylate polymer.

[0040] Examples of commercially available heterocyclic (meth)acrylates (A) include tetrahydrofurfuryl acrylate ("Biscode #150, THFA" manufactured by Osaka Organic Chemical Industry Co., Ltd., "Lite Acrylate THF-A" manufactured by Kyoeisha Chemical Co., Ltd.), tetrahydrofurfuryl methacrylate ("Lite Ester THF (1000)" manufactured by Kyoeisha Chemical Co., Ltd.), (2-methyl-2-ethyl -1,3-dioxolan-4-yl) methyl (meth) acrylate ("MEDOL-10" manufactured by Osaka Organic Chemical Industry Co., Ltd.), cyclic trimethylolpropane formal acrylate ("Biscode #200, CTFA" manufactured by Osaka Organic Chemical Industry Co., Ltd.), tetrahydrofurfuryl alcohol acrylate polymer represented by the following formula ("Biscode #150D" manufactured by Osaka Organic Chemical Industry Co., Ltd.), etc.

[0041] [Chemistry 1]

[0042]

[0043] [(B) Alicyclic (meth)acrylate]

[0044] In the present embodiment, as the component (B), an alicyclic (meth)acrylate (hereinafter referred to as alicyclic (meth)acrylate (B) is used. The alicyclic (meth)acrylate (B) is a compound containing a non-aromatic carbon ring, i.e., an alicyclic hydrocarbon group and a (meth)acryloyl group in the molecule. The alicyclic (meth)acrylate (B) has good wettability with respect to metals and small curing shrinkage, and therefore contributes to the improvement of adhesion.

[0045] The alicyclic hydrocarbon group may be saturated or unsaturated, and is preferably a saturated carbon ring. The alicyclic hydrocarbon group may be monocyclic or polycyclic. The alicyclic hydrocarbon group preferably has 6 or more ring carbon atoms, and more preferably 6 to 10.

[0046] The alicyclic (meth)acrylate (B) may be a multifunctional (meth)acrylate having a plurality of (meth)acryloyl groups, or a monofunctional (meth)acrylate having one (meth)acryloyl group. In the alicyclic (meth)acrylate (B), the (meth)acryloyloxy group may be directly bonded to the alicyclic hydrocarbon group, or may be bonded via a connecting group. In the case of bonding via a connecting group, the (meth)acryloyloxy group may be bonded to the alicyclic hydrocarbon group via an alkanediyl group having 1 to 6 carbon atoms, for example, via a methylene group. In addition to substitution based on the (meth)acryloyloxy group, the alicyclic hydrocarbon group may further have a substituent, or may be unsubstituted. There is no particular limitation on the substituent, and a hydrocarbon group is preferred. For example, the alicyclic hydrocarbon group may have one or more hydrocarbon groups (such as alkyl groups) having 1 to 6 carbon atoms as substituents.

[0047] Examples of the alicyclic (meth)acrylate (B) include:

[0048] (B1) a group having a (meth)acryloyloxy group directly bonded to a substituted or unsubstituted norbornane ring (for example, isobornyl (meth)acrylate),

[0049] (B2) those having a (meth)acryloyloxy group directly bonded to a substituted or unsubstituted cyclohexyl ring (e.g., tert-butylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, cyclohexyl (meth)acrylate),

[0050] (B3) a (meth)acryloyloxy group bonded to a substituted or unsubstituted tricyclodecane ring via an alkanediyl group having 1 to 6 carbon atoms (for example, dimethylol-tricyclodecane di(meth)acrylate),

[0051] (B4) A (meth)acryloyloxy group bonded directly or via an oxyalkylene group having 1 to 4 carbon atoms to a substituted or unsubstituted dicyclopentenyl ring or dicyclopentanyl ring (e.g., dicyclopentenyloxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate)

[0052] Etc. These may be used alone or in combination of two or more.

[0053] In one embodiment, the alicyclic (meth)acrylate (B) may be at least one selected from the group consisting of isobornyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, cyclohexyl (meth)acrylate, dihydroxymethyl-tricyclodecane di(meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate and dicyclopentylalkyl (meth)acrylate.

[0054] Examples of commercially available alicyclic (meth)acrylates (B) include isobornyl acrylate ("Biscode IBXA" manufactured by Osaka Organic Chemical Industry Co., Ltd., "Lite Acrylate IB-XA" manufactured by Kyoeisha Chemical Co., Ltd.), isobornyl methacrylate ("Lite Ester IB-X" manufactured by Kyoeisha Chemical Co., Ltd.), 4-tert-butylcyclohexyl acrylate ("TBCHA" manufactured by KJ Chemical Co., Ltd.), 3,3,5-trimethylcyclohexyl acrylate ("Biscode #196, TMCHA" manufactured by Osaka Organic Chemical Industry Co., Ltd.), cyclohexyl acrylate ( "Biscode #155, CHA" manufactured by Osaka Organic Chemical Industry Co., Ltd.), dimethylol-tricyclodecane diacrylate ("Lite Acrylate DCP-A" manufactured by Kyoeisha Chemical Co., Ltd.), dicyclopentenyloxyethyl methacrylate ("FA-512M" manufactured by Showa Denko Materials Co., Ltd.), dicyclopentenyl acrylate ("FA-511A" manufactured by Showa Denko Materials Co., Ltd.), dicyclopentenyloxyethyl acrylate ("FA-512A" manufactured by Showa Denko Materials Co., Ltd.), dicyclopentyl acrylate ("FA-513A" manufactured by Showa Denko Materials Co., Ltd.), and the like.

[0055] [(C) (Meth)acrylates other than the above-mentioned components (A) and (B)]

[0056] In the present embodiment, as the component (C), a (meth)acrylate having a molecular weight or weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2 (hereinafter referred to as (meth)acrylate (C)) other than the above-mentioned components (A) and (B) is used. The (meth)acrylate (C) contributes to improving the adhesion by being mixed with the components (A) and (B). In addition, the (meth)acrylate (C) may be used alone or in combination of two or more having the above-mentioned molecular weight and functional group number.

[0057] Here, regarding the above molecular weight or weight average molecular weight, when the (meth)acrylate (C) is a compound having a single structure, the molecular weight is used, and when it has a molecular weight distribution such as a polymer or an oligomer, its weight average molecular weight (Mw) is used. By making the molecular weight or weight average molecular weight of the (meth)acrylate (C) above 200, flexibility is imparted to the cured product, thereby improving the adhesion to metals and the like. The weight average molecular weight of the (meth)acrylate (C) is measured by gel permeation chromatography (GPC method) under the following conditions, and can be calculated based on the dissolution time of the measured sample using a standard curve prepared based on the molecular weight and dissolution time of standard polystyrene.

[0058] Column: TSKgel Hxl (Tosoh Corporation)

[0059] Mobile phase: Tetrahydrofuran (THF)

[0060] Mobile phase flow rate: 1.0mL / min

[0061] Column temperature: 40°C

[0062] Injection volume: 50μL

[0063] Sample concentration: 0.2 mass%

[0064] By using a (meth)acrylate (C) having a functional group of 1 or 2, flexibility is imparted to the cured product, and adhesion to metals, etc. can be improved. As the (meth)acrylate (C), only a (meth)acrylate having a functional group of 1 or 2 may be used, or a (meth)acrylate having a functional group of 1 and a (meth)acrylate having a functional group of 2 may be used in combination.

[0065] As the (meth)acrylate (C), it is preferred to use (C1) a polybutadiene structure-containing (meth)acrylate and / or (C2) a urethane (meth)acrylate. That is, in one embodiment, the (meth)acrylate (C) preferably includes at least one selected from the group consisting of (C1) a polybutadiene structure-containing (meth)acrylate having a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2, and (C2) a urethane (meth)acrylate having a molecular weight or weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2.

[0066] The (meth)acrylate containing a polybutadiene structure of the component (C1) is a (meth)acrylate having a polybutadiene structure, and examples thereof include: a (meth)acryloyl group having a terminal of a polybutadiene molecule, and a (meth)acrylate containing a hydroxyl group reacting with a polyisocyanate and a polyol having a hydroxyl group at a terminal of a polybutadiene molecule, and further reacting the hydroxyl group-containing (meth)acrylate. The double bonds of the polybutadiene skeleton may be hydrogenated. The number of functional groups of the component (C1) is preferably difunctional, and for example, polybutadiene di(meth)acrylate having a (meth)acryloyl group at both terminals of polybutadiene can be preferably used.

[0067] The weight average molecular weight of the (meth)acrylate of the component (C1) is preferably 1,000 to 30,000, more preferably 3,000 to 20,000, and even more preferably 5,000 to 15,000.

[0068] (C2) The urethane (meth)acrylate of the component is a compound having a (meth)acryloyl group and a urethane bond in the molecule.

[0069] Examples of the urethane (meth)acrylate as the component (C2) include: (C2-1) those obtained by reacting (meth)acrylic acid with a urethane prepolymer containing a terminal hydroxyl group, wherein the urethane prepolymer containing a terminal hydroxyl group is obtained by reacting a polyol with a polyisocyanate; (C2-2) those obtained by reacting a hydroxyl-containing (meth)acrylate with a urethane prepolymer containing a terminal isocyanate group, wherein the urethane prepolymer containing a terminal isocyanate group is obtained by reacting a polyol with a polyisocyanate; (C2-3) those obtained by reacting a hydroxyl-containing (meth)acrylate with an isocyanate compound; and the like.

[0070] Examples of the polyol in the component (C2) include polyether polyols, polyester polyols, polycarbonate polyols, etc. Examples of the polyisocyanate include aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, etc. Examples of the hydroxyl-containing (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, etc.

[0071] Regarding the number of functional groups of the component (C2), (C2-1) and (C2-2) are preferably difunctional, and (C2-3) is preferably monofunctional.

[0072] Regarding the molecular weight or weight average molecular weight of the (meth)acrylate of the component (C2), the weight average molecular weight of (C2-1) and (C2-2) is preferably 1,000 to 30,000, more preferably 5,000 to 30,000, and even more preferably 10,000 to 30,000. The molecular weight or weight average molecular weight of (C2-3) is preferably 200 to 5,000, more preferably 200 to 2,000, and even more preferably 200 to 1,000.

[0073] When the curable composition contains both the component (C1) and the component (C2) as the component (C), the mass ratio (C1) / (C2) of the contents of the component (C1) and the component (C2) is not particularly limited, but is preferably 0.2 to 5, more preferably 0.3 to 3, and may be 0.4 to 1. Here, when the component (C1) and the component (C2) are used in combination, the component having a (meth)acryloyl group and a urethane bond and a polybutadiene structure is used as the component (C1) instead of the component (C2), and the mass ratio (C1) / (C2) is calculated.

[0074] [(D) Polymerization initiator]

[0075] The curable composition of the present embodiment may further include (D) a polymerization initiator. As the (D) polymerization initiator, there is no particular limitation as long as it can initiate free radical polymerization of the above-mentioned (A) component, (B) component, and (C) component. The (D) polymerization initiator may be (D1) a photopolymerization initiator, or (D2) a thermal polymerization initiator, or both.

[0076] (D1) As a photopolymerization initiator, an alkylphenone compound, an acylphosphine oxide compound, an oxime ester compound, a thioxanthone compound, an anthraquinone compound etc. are mentioned, for example. These can be used individually or in combination of 2 or more types.

[0077] Examples of the alkylphenone compound include benzyl methyl ketal compounds such as 2,2'-dimethoxy-1,2-diphenylethane-1-one, α-hydroxyphenyl alkyl ketone compounds such as 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropane-1-one, and aminoalkyl phenone compounds such as 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one and 2-benzylmethyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone. Examples of the acylphosphine oxide compound include phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide. These may be used alone or in combination of two or more.

[0078] Examples of the (D2) thermal polymerization initiator include azo compounds such as azobisisobutyronitrile (AIBN) and 1,1'-azobis(cyclohexanecarbonitrile) (ABCN), and organic peroxides such as di-tert-butyl peroxide, tert-butyl hydroperoxide, tert-butyl peroxyvalerate, benzoyl peroxide, and methyl ethyl ketone peroxide. These can be used alone or in combination of two or more.

[0079] When the polymerization initiator (D) contains both the photopolymerization initiator (D1) and the thermal polymerization initiator (D2), the mass ratio (D1) / (D2) of the content of the component (D1) to the component (D2) is not particularly limited, but is preferably 0.3 to 10, more preferably 0.5 to 5, and may also be 1 to 3.

[0080] [(E) Cross-linking agent]

[0081] The curable composition of the present embodiment may further include (E) a crosslinking agent. As a crosslinking agent, for example, a trifunctional or higher (meth)acrylate may be cited. Specifically, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, etc. may be cited. Any one of these may be used or two or more may be used in combination.

[0082] [Other additives]

[0083] In addition to the above-mentioned components, the curable composition of the present embodiment may also contain additives such as antioxidants, polymerization inhibitors, colorants, and mildewproofing agents as needed within the scope that does not impair the purpose of the present embodiment. In addition, within the scope that does not impair the purpose of the present embodiment, the curable composition may contain (meth)acrylates other than the above-mentioned components (A), (B), (C), and (E).

[0084] [Curable composition]

[0085] In the curable composition of the present embodiment, the content of component (A) and component (B) is set as follows. Relative to 100 parts by mass of the total content of component (A), component (B) and component (C), the total content of component (A) and component (B) is 70 parts by mass to 95 parts by mass. Therefore, relative to the above-mentioned total content of 100 parts by mass, the content of component (C) is 5 parts by mass to 30 parts by mass. By making the total content of component (A) and component (B) more than 70 parts by mass, it is possible to improve adhesion, especially to improve adhesion to metal. In addition, by making the total content less than 95 parts by mass, it is possible to give flexibility to the cured product and improve adhesion.

[0086] In the curable composition, the mass ratio (A) / (B) of the content of the component (A) to the content of the component (B) is 0.6 to 20. By making (A) / (B) 0.6 or more, the adhesion to metal can be improved. By making (A) / (B) 20 or less, the strength can be improved. (A) / (B) is preferably 0.7 to 16, and more preferably 0.8 to 10.

[0087] The curable composition may contain only the components (A), (B) and (C), but usually further contains a polymerization initiator (D). The content of the component (D) relative to 100 parts by mass of the total content of the components (A), (B) and (C) is not particularly limited, but is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and may also be 1 to 3 parts by mass.

[0088] When the curable composition contains (E) a crosslinking agent, the content of the (E) crosslinking agent is not particularly limited, and for example, it may be 0.1 to 10 parts by mass, 0.3 to 5 parts by mass, or 0.5 to 3 parts by mass relative to 100 parts by mass of the total content of the (A) component, the (B) component, and the (C) component.

[0089] The total content of the components (A), (B) and (C) relative to 100% by mass of the curable composition is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more. The upper limit of the total content of the components (A), (B) and (C) is not particularly limited, and may be, for example, 99.9% by mass or less, 99.5% by mass or less, or 99% by mass or less.

[0090] The curable composition of the present embodiment is cured by light and / or heat to obtain a cured product. Specifically, when a photopolymerization initiator (D1) is included as the polymerization initiator (D), curing is mainly performed by light, and when a thermal polymerization initiator (D2) is included as the polymerization initiator (D), curing is mainly performed by heat.

[0091] The purpose of the curable composition of the present embodiment is not particularly limited, for example, it is preferably used for electrical components such as electronic control unit (ECU) substrates, coils, connectors, etc. In detail, the above-mentioned curable composition is excellent in adhesion to metals such as copper or aluminum, resins such as glass epoxy resins, and has a high volume resistivity, so it is preferably used in the purpose of coating or sealing the exposed portion of the metal in the electrical component. By utilizing the cured product of the curable composition, the exposed portion of the metal is isolated from the outside world containing moisture, so that the metal can be prevented from corroding at the exposed portion. Therefore, the curable composition of the present embodiment is preferably used as a corrosion-resistant resin composition for electrical components. In addition, by making the cured product have a high volume resistivity, it can also be used as an insulating sealing resin composition in electrical components.

[0092] Example

[0093] Hereinafter, the curable composition will be described in detail based on Examples, but the present invention is not limited thereto.

[0094] The raw materials used in Examples and Comparative Examples are shown below.

[0095] [Heterocyclic (meth)acrylate (A)]

[0096] THFA: Tetrahydrofurfuryl acrylate ("Biscode #150, THFA" manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0097] CTFA: Cyclic trimethylolpropane formal acrylate ("Biscot #200, CTFA" manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0098] [Alicyclic (meth)acrylate (B)]

[0099] IBXA: Isobornyl acrylate ("Biscoate IBXA" manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0100] ·TBCHA: 4-tert-butylcyclohexyl acrylate ("TBCHA" manufactured by KJ Chemical Co., Ltd.)

[0101] [(Meth)acrylate (C)]

[0102] BAC-45: polybutadiene diacrylate represented by the following formula ("BAC-45" manufactured by Osaka Organic Chemical Industry Co., Ltd., Mw: 10,000, number of functional groups: 2)

[0103] [Chemistry 2]

[0104]

[0105] UN6207: Polyether urethane acrylate ("UN-6207" manufactured by Negami Industries, Ltd., Mw: 27000, number of functional groups: 2)

[0106] · KRM9276: Urethane acrylate ("KRM9276" manufactured by Dicel Olex Co., Ltd., Mw: 215, number of functional groups: 1)

[0107] [Initiator (D)]

[0108] Initiator 1: α-Hydroxyalkylphenone (“Omnirad 184” manufactured by IGM Resins BV)

[0109] Initiator 2: diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide ("Omnirad TPO" manufactured by IGM Resins BV)

[0110] Initiator 3: tert-Butyl peroxyvalerate ("Parbcil PV" manufactured by NOF Corporation)

[0111] [Other ingredients]

[0112] Methyl acrylate: molecular weight 86

[0113] ·TMPTA: trimethylolpropane triacrylate (crosslinking agent, molecular weight: 296.3, number of functional groups: 3)

[0114] [Example 1 to Example 17 and Comparative Example 1 to Comparative Example 16]

[0115] According to the compounding (mass parts) shown in Tables 1 to 3 below, the components were mixed and stirred to prepare curable compositions of Examples 1 to 17 and Comparative Examples 1 to 16. "A+B+C" in the table represents the total mass parts of component (A), component (B) and component (C). "A+B" represents the total mass parts of component (A) and component (B) relative to 100 mass parts of the total content of component (A), component (B) and component (C). "A / B" represents the mass ratio of the content of component (A) to the content of component (B).

[0116] Adhesion, tensile strength, tensile elongation, and specific volume resistivity of each curable composition were measured and evaluated. The measurement and evaluation methods are as follows.

[0117] [Adhesion]

[0118] Copper plates, aluminum plates and glass epoxy substrates were used as substrates. Each curable composition was applied to the substrate with a thickness of 100 μm using a rod coater, and an ultraviolet (UV) irradiation device was used as a curing device to cure the curable composition. As the UV irradiation device, a belt conveyor type UV curing device (trade name CSN2-40A, manufactured by GS Yuasa Co., Ltd.) equipped with a metal halide lamp was used. Regarding the irradiation conditions, the cumulative illuminance was set to 2000 mJ / cm 2 . The cured product (cured product layer) on the substrate was subjected to a checkerboard test as specified in (Japanese Industrial Standard) JIS-K5600-5-6:1999, and the adhesion was evaluated based on the number of remaining squares. The number of remaining squares was evaluated as × when less than 60 squares were left, △ when more than 60 squares were left but less than 90 squares, and ○ when more than 90 squares were left. The adhesion to the glass epoxy substrate, copper plate, and aluminum plate was expressed as "Adhesion GFRP", "Adhesion Cu", and "Adhesion Al", respectively.

[0119] [Tensile strength, tensile elongation]

[0120] The tensile test was carried out by a universal testing machine, and the tensile strength (MPa) and tensile elongation (%) were evaluated. In detail, a release agent was applied to a stainless steel plate, and a 12 cm × 12 cm fence was made on it using a backing member. A specified amount of liquid of the curable composition was placed in such a way that the thickness of the cured product reached 1 mm, and it was cured using an LED-UV irradiator. The obtained cured product sheet was punched out using a dumbbell to make a test piece for the tensile test. A tensile test (tensile speed: 200 mm / min) was carried out using an Autograph (precision universal testing machine) of Shimadzu Corporation, and the strength (tensile strength) and elongation (tensile elongation) of the test piece at break were measured. A tensile strength of 1 MPa or more was evaluated as ○, and a tensile strength of less than 1 MPa was evaluated as ×. A tensile elongation of 10% or more was evaluated as ○, and a tensile elongation of less than 10% was evaluated as ×.

[0121] [Volume specific resistivity]

[0122] A release agent was applied to the stainless steel plate, and a 6 cm × 6 cm fence was made on it using a backing material. A predetermined amount of liquid curable composition was added so that the thickness of the cured product reached 1 mm, and the cured product was cured using an LED-UV irradiator. The volume resistivity of the obtained cured product sheet was measured using a digital ultra-high resistance / micro current meter from ADCMT. As a standard for good insulation, a volume resistivity of 1.0 × 10 14 The value greater than Ω·cm was evaluated as ○, and the value less than Ω·cm was evaluated as ×.

[0123] [Table 1]

[0124]

[0125]

[0126] [Table 2]

[0127]

[0128]

[0129] [Table 3]

[0130]

[0131] The results are shown in Tables 1 to 3. In Comparative Examples 1 and 10, although components (A) to (C) are included, the total amount of components (A) and (B) is small, so the adhesion to metal is poor. In Comparative Examples 2, 4 to 7, since component (B) is not included, the tensile strength is poor, and in Comparative Examples 2, 5 and 7, since the total amount of components (A) and (B) is small, the adhesion to metal is also poor.

[0132] Since the (A) component is not included in Comparative Examples 3, 8, and 9, and the (C) component is not included in Comparative Examples 9, 11, 14, 15, and 16, the adhesion is poor. In Comparative Example 12, although the (A) component to the (C) component is included, the tensile strength is poor because the A / B ratio is larger than the prescribed ratio. In Comparative Example 13, the adhesion to the metal is poor because the A / B ratio is smaller than the prescribed ratio. In Comparative Examples 4, 5, 15, and 16, the volume resistivity is small and the insulation is poor.

[0133] In contrast, Examples 1 to 17 were excellent in adhesion and tensile strength. In addition, the tensile elongation was maintained, the volume resistivity was large, and the insulation properties were present.

[0134] In addition, for various numerical ranges described in the specification, the upper and lower limits of these values ​​can be arbitrarily combined, and all combinations of these values ​​are described in the specification as preferred numerical ranges. In addition, the description of a numerical range such as "X to Y" means greater than X and less than Y.

[0135] Several embodiments of the present invention have been described above, but these embodiments are provided as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. These embodiments or their omissions, substitutions, and changes are included in the scope or purpose of the invention, and are also included in the invention described in the scope of the patent application and its equivalent.

Claims

1. A curable composition, characterized in that Include: (A) a heterocyclic (meth)acrylate having a five-membered or six-membered heterocyclic ring containing an oxygen atom; (B) alicyclic (meth)acrylate; and (C) (meth)acrylate, which is a (meth)acrylate other than the above-mentioned component (A) and the above-mentioned component (B), and has a molecular weight or a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2, The total content of the component (A) and the component (B) is 70 to 95 parts by mass relative to 100 parts by mass of the total content of the component (A), the component (B) and the component (C), The mass ratio (A) / (B) of the content of the component (A) to the content of the component (B) is 0.6 to 20.

2. The curable composition according to claim 1, wherein The component (C) contains a (meth)acrylate having a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2 and containing a polybutadiene structure.

3. The curable composition according to claim 1, wherein The component (C) contains a urethane (meth)acrylate having a molecular weight or a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2.

4. The curable composition according to claim 1, wherein The (C) component includes a polybutadiene structure-containing (meth)acrylate having a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2, and a urethane (meth)acrylate having a molecular weight or a weight average molecular weight of 200 to 30,000 and a functional group number of 1 or 2.

5. The curable composition according to claim 1, wherein The heterocyclic ring of the component (A) is a saturated heterocyclic ring.

6. The curable composition according to claim 1, wherein The total content of the component (A), the component (B), and the component (C) is 80% by mass or more relative to 100% by mass of the curable composition.

7. The curable composition according to claim 1, wherein The curable composition is used for electrical parts.

8. A solidified product, characterized in that: The curable composition according to any one of claims 1 to 7 is cured.

9. An electrical component, characterized in that: The cured product according to claim 8 is included.